Variant rs9939609 in the FTO gene is associated with body mass index among Chinese children - Liu Ailing; Zhang Qian; Hu Xiaoqi; Du Songming; Li Yanping; Fang Hongyun; Ma Guansheng (BMC Medical Genetics, 2010)
Abstract Background Fat-mass and obesity-associated (FTO) gene is a gene located in chromosome region 16q12.2. Genetic variants in FTO are associated with the obesity phenotype in European and Hispanic populations. However, this association still remains controversial in Asian population. We aimed to test the association of FTO genetic variants with obesity and obesity-related metabolic traits among children living in Beijing, China. Methods We genotyped FTO variants rs9939609 in 670 children (332 girls and 338 boys) aged 8-11 years living in Beijing, and analyzed its association with obesity and obesity-related metabolic traits. Overweight and obesity were defined by age- and sex-specific BMI reference for Chinese children. Obesity-related metabolic traits included fasting plasma glucose, lipid profiles, leptin, ghrelin, adiponectin and blood pressures. Results The frequency of rs9939609 A allele was 12.2%, which was 21.9% for the heterozygote and 1.2% for the homozygote of the A allele. The obesity prevalence among the carriers of AA/AT genotypes was significantly higher than that among those with TT genotype (36.4% vs. 22.6%, P = 0.004). Compared to the carrier of TT genotype, the likelihood of obesity was 1.79 (95% confidence interval (95% CI) 1.20-2.67, P = 0.004) for the carrier of AA/AT genotype, after adjustment of sex, age and puberty stages. The BMI Z-score of children with AA/AT genotype were significantly higher than that of their counterparts with the TT genotype (1.1 ± 0.1 vs. 0.8 ± 0.1, P = 0.02). The concentration of triglyceride was 1.03 ± 0.52 mmol/L among TT carrier and 1.13 ± 0.68 mmol/L among AA/AT carrier (P = 0.045). While, the concentrations of adiponectin were 18.0 ± 0.4 μg/ml among carriers of TT and 16.2 ± 0.7 μg/ml among subjects with AA/AT genotype (P = 0.03). The level of glucose marginally increased in the AA/AT genotype subjects (4.67 ± 0.40 mmol/L vs. 4.60 ± 0.35 mmol/L, P = 0.08). The evidence of association was reduced after adjustment for BMI (P = 0.38 for triglyceride, P = 0.20 for adiponectin and glucose). There was weak evidence of association between rs9939609 and other obesity-related metabolic traits including total cholesterol (3.92 ± 0.03 mmol/L vs. 4.02 ± 0.05 mmol/L, P = 0.10), insulin (2.69 ± 1.77 ng/ml vs. 3.12 ± 2.91 ng/ml, P = 0.14), and insulin resistance (HOMA-IR 0.56 ± 0.03 vs. 0.66 ± 0.05, P = 0.10). Conclusions Genetic variation in the FTO gene associates with obesity in Chinese children.